Behind barbed wire : a history of concentration camps from the reconcentrados to the Nazi system, 1896-1945 - Lindsay, Deborah G. 1951- (Universal Publishers, 2020)
The Origination of Concentration Camps: Reconcentrados in Cuba -- The U.S. Military vs. the Filipinos -- American Indian Reservations -- British Refugee Camps during the Boer War -- German Concentration Camps in South West Africa -- The Soviet Gulag -- Military Necessity and Institutional Extremism -- A Climate of Bigotry: The Persecution of European Jews -- The "Aryan Race" vs. the "Undesirables" -- The Nazi Concentration Camp System -- Yellow Peril: The Japanese Internment Camps -- Lesser Known Concentration Camps.